2013
DOI: 10.3109/07435800.2013.844163
|View full text |Cite
|
Sign up to set email alerts
|

MC4R rs17782313gene polymorphism was associated with glycated hemoglobin independently of its effect on BMI in Japanese: the Shimane COHRE study

Abstract: MC4R rs17782313 was associated with obesity and could confer a certain susceptibility to T2D that could be independent of its pro-obesity effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…The further meta-analysis combining previous and our current findings supported the above finding and gave a more precise estimate of the effect of MC4R on type 2 diabetes in Chinese by raising the sample size to 15 462 diabetic patients and 13 865 controls. In addition, our results were in accordance with a previous meta-analysis involving multiethnic populations by Xi et al [10] .Notably, a recent study in Japanese found that rs17782313 was related to glycated hemoglobin, which could be used in type 2 diabetes screening in populations independent of BMI, indicating the potential value of MC4R in type 2 diabetes prediction [39] .…”
Section: Discussionsupporting
confidence: 92%
“…The further meta-analysis combining previous and our current findings supported the above finding and gave a more precise estimate of the effect of MC4R on type 2 diabetes in Chinese by raising the sample size to 15 462 diabetic patients and 13 865 controls. In addition, our results were in accordance with a previous meta-analysis involving multiethnic populations by Xi et al [10] .Notably, a recent study in Japanese found that rs17782313 was related to glycated hemoglobin, which could be used in type 2 diabetes screening in populations independent of BMI, indicating the potential value of MC4R in type 2 diabetes prediction [39] .…”
Section: Discussionsupporting
confidence: 92%
“…Mutombo et al demonstrated that the carriers of the T/C + C/C genotypes of the MC4R rs17782313 polymorphism had a visibly higher BMI and higher levels of glycated haemoglobin than those with the T/T genotype, even after taking into account such variables as age and gender. Proneness to type 2 diabetes in this group was not linked to a tendency to obesity [12]. A study of the Chinese population, on the other hand, suggested a relationship between the C/T genotype of the MC4R rs17782313 polymorphism and a higher waist-to-hip ratio, even after multiple testing correction [30].…”
Section: Discussionmentioning
confidence: 62%
“…One more genetic factor that substantially contributes to obesity -thus predisposing to carbohydrate metabolism disorders and type 2 diabetes -is the melanocortin-4 receptor (MC4R) rs17782313 polymorphism [12]. It is considered to play an important part in the regulation of food intake, and maintenance of long-term energy homeostasis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Melanocortin-4 receptor, which is coded by the MC4R gene, is a key protein in regulation of energy balance, adiposity, and glucose metabolism 10 , 16 , 17 . The common variants in the MC4R gene have been previously related to measures of glucose metabolism such as insulin resistance 16 , insulin sensitivity 11 , and HbA1c 19 . Our data suggest that the MC4R genotype may also play a role in regulating postpartum change patterns of glycemic profiles caused by pregnancy.…”
Section: Discussionmentioning
confidence: 99%